The Consumption, Physical Activity, And Nutrition Status to Blood Cholesterol of Participants in Posbindu Anggrek Rosalina, Cibodas Baru, Tangerang - Nanang Prayitno; Nila Dania Nardhiana; Ahmad Faridi; Meilinasari Meilinasari; Sugeng Wiyono (Politeknik Kesehatan Kemenkes Jakarta II, 2018)
One of the changes with increasing age is the increase in total blood cholesterol levels. The purpose of this research is to know the relationship of the consumption level of (energy, fat, and cholesterol), physical activity, and nutritional status with total blood cholesterol of the participants of Posbindu Anggrek Rosalina 45-59 years old in Kelurahan Cibodas Baru Tangerang City 2015.This research use cross sectional design with population of all participants Posbindu Anggrek Rosalina age 45-59 years Kelurahan Cibodas Baru Tangerang City Year 2015. Sampling using purposive sampling technique and obtained 41 respondents. The results showed that average energy consumption was 1806.38 Calories / day, fat consumption level 71.84 gr / day, cholesterol consumption 238.87 mg / day, physical activity 1.49, nutritional status (BMI) 25.70 (overweight), and total blood cholesterol 212.66 mg / dl.Pearson correlation test showed that there was a significant correlation between energy consumption level (p = 0.045 <α = 0.05), fat consumption level (p = 0.039 <α = 0.05), and cholesterol consumption level (p = 0.016 <α = 0.05) with total blood cholesterol levels. There was no significant relationship between physical activity (p = 0.273> α = 0.05), whereas there was no correlation between nutritional status (p = 0.597> α = 0.05) with total blood cholesterol level.